(untitled) (Biological Sciences - PJSIR, 1995)
tified by comparison with their standard samples in the GC and fragmentation pattern of the individual component in the mass spectra [5-6]. The percentage composition was found by gas chromatography on the basis of peak areas. The compounds of lower content (less than 0.1%) were not identified